BILANGAN DOMINASI-LOKASI HASIL KALI SISIR GRAF LINTASAN DENGAN BEBERAPA GRAF REGULER - Sibua, Aulia; Gafur, Anuwar Kadir Abdul (Universitas Pasifik Morotai, 2022)
To all the paper, all graph is connected, simple, undirected, and finite. A set vertex W of is called the domination set if every vertex for every is adjacent to some vertex The minimum cardinality of a location-dominated set is called the location-dominated number, which is denoted by λ(G). In this research, we observe to the comb product of a path graph to regular graphs. If noticed to the definition of a regular graph, then obtained a complete graph is graph with order . So in the results of this research we start by looking for the location-dominated number of the comb product of a path graph with a regular graph where the regular graph is a , end which each one has , , dan where order end .